S. 2020 RE: SMOKING CESSATION 'DEMONSTRATION PROJECT' FOR FEDERAL EMPLOYEES (Tufts Archival Research Center, 2007)
Letter from Gregory R. Scott to Gene A. Knorr regarding a bill requring federal employees to see a demonstration project discouraging them from using tobacco, alcohol, and other chemical substances. Discusses the history of the bill as well as all the people associated with it. States that, while the provision including encouragement of "smoking cessation" may not be beneficial right now, it could possibly help deter any more similar actions in the future.